Gel spacer to protect carotid artery and reconstructed jejunum in image-guided interstitial brachytherapy for recurrent hypopharyngeal cancer: a technical report - Murakami, Naoya; Honma, Yoshitaka; Yoshimoto, Seiichi; Shima, Satoshi; Kashihara, Tairo; Takahashi, Kana; Kaneda, Tomoya; Inaba, Koji; Okuma, Kae; Masui, Koji; Yoshida, Ken; Igaki, Hiroshi; et al. (Journal of Contemporary Brachytherapy, 2021)
In this technical report, patient with total pharyngolaryngectomy and jejunum interposition experienced lymph node metastasis in the reconstructed mesenteric lymph nodes. Because this patient received 45 Gy of whole neck radiation therapy 24 years ago and small bowel’s tolerance dose of the reconstructed jejunum was considered to be low, spacer gel injection was applied during image-guided interstitial brachytherapy to decrease doses to the reconstructed jejunum and previously irradiated carotid artery.